Managing Inclusive Education Services for Children with Special Needs: Evidence from Muhammadiyah Elementary School in Indonesia - Isyatul Karimah; Suyatno Suyatno; Sukirman Sukirman (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2026)
This study aims to explore the management of inclusive education services for children with special needs in Muhammadiyah Elementary School in Bontang City, East Kalimantan. This research employed a qualitative exploratory approach involving observations, in-depth interviews, and document analysis. The participants consisted of school principals, teachers, shadow teachers, parents, and students with special needs selected through purposive sampling. The findings reveal four main aspects of inclusive service management: policy and planning, service organization and implementation, monitoring and evaluation, and challenges in implementation. The study found that effective inclusive education management requires strong collaboration among schools, parents, psychologists, and therapists, supported by adaptive curriculum and structured evaluation mechanisms. However, several challenges remain, including limited teacher training and insufficient disability-friendly infrastructure. This study contributes to the development of a practical management framework for inclusive education services in elementary schools. Keywords: children with special needs, inclusive education, inclusive services management, muhammadiyah elementary school,